WASP-135b: A Highly Irradiated, Inflated Hot Jupiter Orbiting a G5V Star. (14th January 2016) - Spake, J. J.; Brown, D. J. A.; Doyle, A. P.; Hébrard, G.; McCormac, J.; Armstrong, D. J.; Pollacco, D.; Chew, Y. Gómez Maqueo; Anderson, D. R.; Barros, S. C. C.; Bouchy, F.; Boumis, P.; et al.
Abstract: We report the discovery of a new transiting planet from the WASP survey. WASP-135b is a hot Jupiter with radius 1.30 ± 0.09 R Jup, mass 1.90 ± 0.08 M Jup, and an orbital period of 1.401 days. Its host is a Sun-like star, with a G5 spectral type and a mass and radius of 0.98 ± 0.06 M ☉ and 0.96 ± 0.05 R ☉, respectively. The proximity of the planet to its star means that WASP-135b receives high levels of insolation, which may be the cause of its inflated radius. Additionally, we report weak evidence of a transfer of angular momentum from the planet to its host star.